Study of clinical and biochemical profile of acute alcoholic liver disease in a teaching hospital in Telangana - Khatroth, Shamsunder (International Journal of Advances in Medicine, 2018)
Background: Chronic alcohol consumption gives rise to various health risks that include liver disease, heart disease, pancreatitis, central nervous system disorders and certain forms of cancer. Alcoholic liver disease (ALD) is a spectrum of clinicopathological abnormalities, reflecting an acute or chronic inflammation of the liver parenchyma induced by alcohol use. It is associated with changes in various biochemical parameters and also various clinical manifestations in the patients. The objective of the present study to evaluate clinical and biochemical profile of acute alcoholic liver disease. Methods: The prospective hospital-based case control study was done at MNR Medical College, in the department of General Medicine for duration of one year from March 2017 to April 2018. A total of 120 cases diagnosed clinically and biochemically as Acute alcoholic liver disease were included in the study. Results: The age group ranged from 20 to 60 years and the male to female ratio was 2.42. Majority of the patients were in the age group of 30-40 years (54.1%). Majority of the patients (66.6%) consumed >60 grams/24hours of alcohol. Jaundice, nausea and vomiting were seen in 83.3% cases followed by hepatomegaly in 66.6% cases. Majority of them had been consuming alcohol for more than 5 years. Conclusions: Chronic alcohol consumption is more common in adult males. Chronic alcoholics consume more amount of alcohol. Alcoholic liver disease has a varied clinical presentation and is associated with deranged biochemical parameters.